Teacher’s perspectives on collaboration and professional development in Portuguese schools - Unas, Maria Manuela (2019)
This paper is part of a broader international research project, which includes eight case studies carried out in public schools in Portugal and in Chile. It is a comparative study, which aims to understand the way teachers describe formal and informal opportunities for collaboration in their schools and its effect in terms of practical knowledge; to identify the enablers and inhibitors that influence professional collaborative learning at school; to understand the role of teacher evaluation and student academic results on teacher's professional development; to analyse how teachers with differents skills, experiences and schools view their own professional development. In this case study, a public school, located in the north of Portugal, with sixty years of history, was selected. The participants in the study are teachers from different disciplinary areas and teaching departments. The school includes elementary and secondary school level, with regular and professional study programmes. Data collection is based on semi-structured interviews to the school director and to eight teachers, mainly coordinators of teaching departments. Results based on findings from teachers point out the importance of collaborative work, but they also recognize that schools need a reorganization that includes time for this purpose, integrated on teacher's schedule. Informal opportunities are also seen as fundamental for professional development and to improve student outcomes. Conclusions and implications for teacher collaboration and professional development will be discussed in the paper.